LICHTENSTEIN YÖNTEMİ İLE İNGUİNAL HERNİ ONARIMI - YAVUZ, Nihat; ÜNAL, Ethem; DERVİŞOĞLU, Adem; TORTUM, Osman Baran (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Lichtenstein’s tension free technique presents many important advantages in the repair of inguinal hernia. It is easy to perform, recovery is quick and the results, thus far, are superb. Between December 1994 and July 1998, in Gorbon Unit of General Surgery Clinic in Cerrahpasa School of Medicine, Istanbul University 47 Lichtenstein.s inguinal herniorraphy operation was performed on 38 patients and the early results were evaluated retrospectively. Results.- In the postoperative period, none of our cases experienced pain requiring narcotic analgesics. Oral intake was allowed few hours following the operation and patients were mobilized on the first postoperative day. In one case, subcutaneous infection developed and it was treated successfully with drainage and antibiotics. The average postoperative hospital stay period was 3.2 days (2-5). All of the patients were pleased of postoperative comfort. During a mean follow-up of 48-months (15-60), no other complication like mesh rejection, testicular atrophy or recurrence was seen. Conclusion.- Lichtenstein.s tension free technique is a simple and effective method as it provides many advantages from the point of view of pain, mobilization and operation time.